Croatian Dependecy Treebank in Multilingual Context - Tadić, Marko (Array, 2006)
This paper presents the work in progress of building of the Croatian Dependency Treebank. Its design principles, procedures and the pilot corpus used within are described. It also discusses its possible usage in combination with other similar treebanks in multilingual applications such as transfer of syntactic annotation in parallel corpora. Perspectives for further development of Croatian Dependecy Treebank are presented at the end.